Peritoneal dialysis from basic concepts to clinical excellence - Ronco, Claudio 1951-; Crepaldi, Carlo; Cruz, Dinna N. (Karger, 2009)
The importance of peritoneal dialysis (PD) in the therapy of chronic kidney disease has been steadily increasing. The simultaneous advancement in clinical practice and basic research has increased overall knowledge and led to significant progress in the safe and adequate application of PD. Moreover, integration with other techniques in the therapy of uremia represents an important step in the optimization of the whole program of renal replacement therapy.Leading experts in the field have contributed to this volume, discussing topics such as the biology of the peritoneal membrane, dialysis solutions, inflammation and nutrition, PD adequacy, or complications and their management or PD in special settings. This compilation updates and expands the information on PD published in previous volumes of the series ‘Contributions to Nephrology’. It represents an important source of information for beginners and experts, basic scientists and clinical physicians, students and investigators who want to have a true update on current research and clinical practice in peritoneal dialysis
Keywords: Nephrology; Biochemistry; Cardiovascular System; Dialysis; Nutrition; Physiology; Peritonealdialyse; Aufsatzsammlung